Rancang Bangun Aplikasi Pencatatan Produksi Pada PT.Mega Utama Indah - Faraby, Muchamad Iqbal; Wibowo, Januar; Setyawan, Henry Bambang (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
PT. Mega Utama Indah is a company engaged in the trading and processing of raw wood into finished wood. The main obstacle faced by PT. Mega Utama Indah now is recording the production process are still done manually such as recording the use of raw materials and auxiliary materials, the use of human labor, the use of the machine, and the use of other costs. All recording is still done by recording into a book.These constraints resulted in companies experiencing difficulties in terms of search data, perform scheduling of engine maintenance, and the difficulty in obtaining information and reports required by the leadership in making decisions for the company, the required application records of production which includes data recording of raw materials, auxiliary materials , human labor, machinery, and other costs.Based on research that has been done, the application can generate reports, such reports raw material usage per order or per month, reports the use of adjuvant per order or per month, reports the use of labor per order or per month, reports the use of machines per order or per month, and report usage fee per order or per month that the company needs to search the data, perform machine maintenance scheduling, and obtain the required information by the leadership in making decisions for the company.